Arterial Oxygenation in Traumatic Brain Injury—Relation to Cerebral Energy Metabolism, Autoregulation, and Clinical Outcome. (September 2021) - Wettervik, Teodor Svedung; Engquist, Henrik; Howells, Timothy; Lenell, Samuel; Rostami, Elham; Hillered, Lars; Enblad, Per; Lewén, Anders
Background: Ischemic and hypoxic secondary brain insults are common and detrimental in traumatic brain injury (TBI). Treatment aims to maintain an adequate cerebral blood flow with sufficient arterial oxygen content. It has been suggested that arterial hyperoxia may be beneficial to the injured brain to compensate for cerebral ischemia, overcome diffusion barriers, and improve mitochondrial function. In this study, we investigated the relation between arterial oxygen levels and cerebral energy metabolism, pressure autoregulation, and clinical outcome. Methods: This retrospective study was based on 115 patients with severe TBI treated in the neurointensive care unit, Uppsala university hospital, Sweden, 2008 to 2018. Data from cerebral microdialysis (MD), arterial blood gases, hemodynamics, and intracranial pressure were analyzed the first 10 days post-injury. The first day post-injury was studied in particular. Results: Arterial oxygen levels were higher and with greater variability on the first day post-injury, whereas it was more stable the following 9 days. Normal-to-high mean pO2 was significantly associated with better pressure autoregulation/lower pressure reactivity index ( P = .02) and lower cerebral MD-lactate ( P = .04) on day 1. Patients with limited cerebral energy metabolic substrate supply (MD-pyruvate below 120 µM) and metabolic disturbances with MD-lactate-/pyruvate ratio (LPR) above 25 had significantly lower arterial oxygen levels than those with limited MD-pyruvate supply and normal MD-LPR ( P = .001) this day. Arterial oxygenation was not associated with clinical outcome. Conclusions: Maintaining a pO2 above 12 kPa and higher may improve oxidative cerebral energy metabolism and pressure autoregulation, particularly in cases of limited energy substrate supply in the early phase of TBI. Evaluating the cerebral energy metabolic profile could yield a better patient selection for hyperoxic treatment in future trials.